Changes in immune function in patients with rheumatoid arthritis following treatment with sodium aurothiomalate. Issue 3 (June 1981) - Highton, J; Panayi, G S; Shepherd, P; Griffin, J; Gibson, T
Abstract : The mitogenic response of peripheral blood lymphocytes from 21 patients with rheumatoid arthritis to concanavalin-A (con--A), phytohaemagglutinin (PHA), and pokeweed mitogen (PWM) was significantly lower than in 30 normal subjects. After 15--24 weeks' treatment with sodium aurothiomalate (GST) the response to these mitogens rose to within the normal range. Improvement over pretreatment values was significant for con-A and PWM measured as area under the dose response curve but only for con--A if response at optimal mitogen concentration is the sole criterion. The improvement in PHA response was not significant with either method of measurement. There was an improvement in disease activity by 15--24 weeks as measured by a fall in serum C-reactive protein (CRP), IgM rheumatoid factor (RF), Clq binding activity (ClqBA), and Ritchie articular index. Con--A lymphocyte responsiveness was inversely related to serum CRP levels, but measurements of disease activity were otherwise unrelated to lymphocyte mitogen responsiveness. The observed improvement in peripheral blood lymphocyte responsiveness during gold treatment contrasts with the suppressive effect of gold in vitro. We suggest that the improvement in lymphocyte function is due to the lessening of rheumatoid disease activity during gold treatment, and that the low serum gold levels in our patients were insufficient to mask this effect. Sera from some of our patients were capable of suppressing the function of normal lymphocytes, and this was less apparent after treatment. The suppressive effect of sera correlated with ClqBA. Suppressive factors in serum, including possibly immune complexes, may be one factor leading to suppression of lymphocyte function during rheumatoid arthritis. Such an inverse relationship between humoral and cellular immune mechanisms might influence the clinical expression of rheumatoid arthritis.